Whole exome sequencing identifies a POLRID mutation segregating in a father and two daughters with findings of Klippel–Feil and Treacher Collins syndromes. (27th October 2014) - Giampietro, Philip F.; Armstrong, Linlea; Stoddard, Alex; Blank, Robert D.; Livingston, Janet; Raggio, Cathy L.; Rasmussen, Kristen; Pickart, Michael; Lorier, Rachel; Turner, Amy; Sund, Sarah; Sobrera, Nara; et al.
<x xml:space="preserve">Abstract</x> We report on a father and his two daughters diagnosed with Klippel–Feil syndrome (KFS) but with craniofacial differences (zygomatic and mandibular hypoplasia and cleft palate) and external ear abnormalities suggestive of Treacher Collins syndrome (TCS). The diagnosis of KFS was favored, given that the neck anomalies were the predominant manifestations, and that the diagnosis predated later recognition of the association between spinal segmentation abnormalities and TCS. Genetic heterogeneity and the rarity of large families with KFS have limited the ability to identify mutations by traditional methods. Whole exome sequencing identified a nonsynonymous mutation in POLR1D (subunit of RNA polymerase I and II): exon2:c.T332C:p.L111P. Mutations in POLR1D are present in about 5% of individuals diagnosed with TCS. We propose that this mutation is causal in this family, suggesting a pathogenetic link between KFS and TCS. © 2014 Wiley Periodicals, Inc.